2019
DOI: 10.1029/2019jb018073
|View full text |Cite
|
Sign up to set email alerts
|

A Thick Negative Polarity Anomaly in a Sediment Core From the Central Arctic Ocean: Geomagnetic Excursion Versus Reversal

Abstract: There are two distinctly different views on Quaternary sedimentation rates in the central Arctic Ocean, namely, that they were on cm/kyr or on mm/kyr scales, largely as a result of divergent interpretations of magnetic reversal stratigraphy. This study provides new evidence to help resolve this controversy in the form of an almost 1-m-thick negative polarity interval located at~1.15 m below the seafloor in a 4.15-m-long sediment core from the Lomonosov Ridge, central Arctic Ocean. This thick polarity anomaly w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 78 publications
(171 reference statements)
0
10
0
Order By: Relevance
“…We recall that a prominent magnetostratigraphic unit was identified in the bottom sediment, while a similarly significant inclination drop can also be traced in the records of previous cores from the MR to the central Arctic Ocean, as described in Section 3.2 (Adler et al., 2009; Cronin et al., 2013; Jakobsson et al., 2000; Liu et al., 2019). As an independent comparison tool, the unique paleomagnetic inclination drop has been used in the interpretation of Arctic Ocean glacial‐interglacial cycles and was attributed to MIS7 (Jakobsson et al., 2003; Xiao et al., 2020).…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations
“…We recall that a prominent magnetostratigraphic unit was identified in the bottom sediment, while a similarly significant inclination drop can also be traced in the records of previous cores from the MR to the central Arctic Ocean, as described in Section 3.2 (Adler et al., 2009; Cronin et al., 2013; Jakobsson et al., 2000; Liu et al., 2019). As an independent comparison tool, the unique paleomagnetic inclination drop has been used in the interpretation of Arctic Ocean glacial‐interglacial cycles and was attributed to MIS7 (Jakobsson et al., 2003; Xiao et al., 2020).…”
Section: Discussionmentioning
confidence: 59%
“…As an independent comparison tool, the unique paleomagnetic inclination drop has been used in the interpretation of Arctic Ocean glacial‐interglacial cycles and was attributed to MIS7 (Jakobsson et al., 2003; Xiao et al., 2020). However, because such a signal may also be triggered by diagenesis processes at the sediment–water interface, we maintain that the assignment of the bottom age is still tentative (Channell & Xuan, 2009; Liu et al., 2019; Xuan & Channell, 2010).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…These difficulties in interpreting palaeomagnetic data in the Arctic led to the exclusion of magnetostratigraphy in the construction of the Arctic Coring Expedition (ACEX, IODP Expedition 302) age model for the Neogene . Some recent studies challenge the ACEX-based age model through U-Th ages (Hillaire-Marcel et al, 2017) and palaeomagnetic interpretations (Liu et al, 2019) that support the low-sedimentation rate scenario of Clark (1970). While some studies (e.g., Spielhagen et al, 2004) of Arctic Ocean sediments assumed inclination changes to be coeval and used them for stratigraphic correlation, more recent studies that placed inclination changes into the lithostratigraphic context of the Arctic Ocean (e.g., O'Regan et al, 2008;Wiers et al, 2019) have confirmed the abnormal nature of the palaeomagnetic record by showing that inclination changes are not stratigraphically coeval.…”
Section: Introductionmentioning
confidence: 99%